STRATEGIC MANAGEMENT OF THE TRIPLE HELIX MODEL: WHAT UZBEKISTAN CAN LEARN FROM THE USA’S EXPERIENCE - Ismoilov Elyorjon Makhamadali Ugli (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  The  study  investigates  the  strategic  management  of  university-industry-government relationships within the framework of the Triple Helix model, aiming  to  explore  the  transition  mechanisms  for  the  Republic  of  Uzbekistan.  By utilizing  comparative  institutional  analysis  and  qualitative  assessment  of  strategic management policies, the analysis reveals a significant gap in the commercialization of  academic  knowledge,  but  exposes  a  “Triple  Helix  productivity  paradox”  in transitioning economies. The high concentration of state-funded higher education is negatively correlated with industrial innovation in all development tiers, reflecting the dominance of isolated academic practices. Besides, institutional landscapes revealed a deficit in “absorptive capacity” for technology transfer. To meet “Digital Uzbekistan -2030”  strategy  targets,  there  is  a  necessity  of  improving  the  quality  of  legislative frameworks, extracting crucial lessons from the USA’s experience, specifically the Bayh-Dole Act.